1984
DOI: 10.1159/000153478
|View full text |Cite
|
Sign up to set email alerts
|

Properdin Factor B (Bf) Polymorphism in Saudi Arabs

Abstract: The distribution of properdin factor B (Bf) phenotypes and the gene frequencies were investigated in 918 Saudi Arabs. A high frequency of the ‘rare’ allele BFS0.7 was observed BfS0.7 = 0.1514). The frequencies of the common Bf alleles (Bf = 0.5174, Bf = 0.3213) are outside the corresponding ranges of Bf5, BfF gene frequencies found in European Caucasoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…BfF is more frequent and BfS less frequent in Saudi Arabs. The frequencies of these alleles in Saudi Arabs lie between those reported for Caucasoids and Negroids (Larsen et al 1981, Klouda et al 1983, Mauff et al 1976, Scherz et al 1977. A prominent feature of this Saudi Arab population is the high frequency of BfS0.7 allele.…”
Section: Factor B (Bf)mentioning
confidence: 52%
See 1 more Smart Citation
“…BfF is more frequent and BfS less frequent in Saudi Arabs. The frequencies of these alleles in Saudi Arabs lie between those reported for Caucasoids and Negroids (Larsen et al 1981, Klouda et al 1983, Mauff et al 1976, Scherz et al 1977. A prominent feature of this Saudi Arab population is the high frequency of BfS0.7 allele.…”
Section: Factor B (Bf)mentioning
confidence: 52%
“…This frequency is the highest reported for a "rare" Bf allotype in any population studied SO far. The results of a larger study of the Bf polymorphism in Saudi Arabs including the present sample is published elsewhere (Klouda et al 1984).…”
Section: Factor B (Bf)mentioning
confidence: 99%
“…However, other populations have yet to be extensively studied and little data are available for comparison. Previous studies have demonstrated major differences in HLA class I, I1 and Ill, gene polymorphisms between Nigerian and Caucasoid populations (Klouda et al, 1983;Okoye et al. 1985).…”
Section: Introductionmentioning
confidence: 92%
“…Few data are at present available on the BF and C3 polymorphisms in Ar abic populations [5][6][7][8][9] and none on the C4 polymorphism. The aim of our investiga tion was to study the BF, C3 and C4 poly morphisms in the Tunisian population and to compare the allele frequencies with those of other populations.…”
mentioning
confidence: 99%